Respuesta :
Answer:
[tex]n=0,\\n=6[/tex]
Step-by-step explanation:
Given [tex]n^2-6n=0[/tex], we can factor out an [tex]n[/tex] from each of the terms on the left side of the equation:
[tex]n(n-6)=0[/tex]
Since we have two factors that multiply to zero, we can set each of them to zero and solve for [tex]n[/tex], because zero multiplied by anything is equal to zero. Therefore, as long as either [tex]n[/tex] or [tex]n-6[/tex] is equal to zero, the other factor can be any real number and the equation would still hold true.
Therefore, we have the following cases:
[tex]\begin{cases}n=0,\\n-6=0\end{cases}[/tex]
Solving, we get:
[tex]\begin{cases}n=0, n=\boxed{0}\\n-6=0, n=\boxed{6}\end{cases}[/tex]
[tex]\\ \sf\longmapsto n^2-6n=0[/tex]
- Take n common
[tex]\\ \sf\longmapsto n(n-6)=0[/tex]
Now
[tex]\\ \sf\longmapsto n=0\:or \:(n-6)=0[/tex]
[tex]\\ \sf\longmapsto n=0\:or \;n=6[/tex]
Hence roots of the equation are 0 and 6 .
More:-
We can solve it through Quadratic formula
[tex]\boxed{\sf x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}}[/tex]